Relationship of self-liking, self-competence with self-reported oral health status among 15-year-old children of Davangere city: A cross-sectional survey - Anjan Giriraju; Nagesh Lakshminarayan (Wolters Kluwer Medknow Publications, 2015)
Introduction: Psychological constructs have been found to have potential effects in the improvement of health. Self-esteem (expressed in the form of sub-constructs: Self-liking and self-competence) is a construct, which makes one realize the self. This in turn will result in positive oral-health-seeking behavior and improvement in oral health status. Aim: To assess the relationship of self-liking, self-competence with self-reported oral health status in children aged 15 years, in Davangere city. Materials and Methods: A descriptive, cross-sectional survey was conducted on 220 15-year-old subjects in Davangere City. Specially designed pro forma containing Romanian self-administered questionnaire to record the self-reported oral health status and Tafarodi's SLC scale to measure self-liking/self-competence was used. Chi-square test was used for statistical analysis. Results: A majority of the participants were found to have moderate self-competence and self-liking and their self-reported oral health status was expressed as "excellent." They reported very less or no untreated decayed teeth and no extracted teeth or gingival bleeding. Conclusion: The participants with better self-competence and self-liking perceived their oral health status as good. They reported lesser incidence of oral diseases and discomfort. Self-esteem and oral health were found to be positively related.